2006
DOI: 10.1366/000370206778664707
|View full text |Cite
|
Sign up to set email alerts
|

In situ Infrared Microspectroscopy of ∼850 Million-Year-Old Prokaryotic Fossils

Abstract: In situ infrared (IR) and Raman microspectroscopy have been conducted on Neoproterozoic, organic-walled microfossils (prokaryotic fossils) in doubly polished, petrographic thin sections in order to detect their spectral signatures. The microfossils are very well preserved and occur in black chert from the approximately 850 million-year-old Bitter Springs Formation, Northern Territory, Australia. Raman microspectroscopy on two species of microfossils, one a filament and the other a coccoid, shows disordered pea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 30 publications
0
34
0
Order By: Relevance
“…Marshall et al, 2005;Igisu et al, 2006Igisu et al, , 2009Igisu et al, , 2014. The absorbance ratio of asymmetric stretching band of aliphatic CH 3 end-methyl versus CH 2 chain-methylene describes the branching index of carbon chains.…”
Section: Micro-ftirmentioning
confidence: 99%
See 1 more Smart Citation
“…Marshall et al, 2005;Igisu et al, 2006Igisu et al, , 2009Igisu et al, , 2014. The absorbance ratio of asymmetric stretching band of aliphatic CH 3 end-methyl versus CH 2 chain-methylene describes the branching index of carbon chains.…”
Section: Micro-ftirmentioning
confidence: 99%
“…-band, and it has been used to describe the branching index of carbon chains in fossilized carbonaceous material (Igisu et al, 2006(Igisu et al, , 2009Qu et al, 2015). It has been proposed that the R 3/2 ratio shows systematic variations between biomass of archaeans, bacteria, and eukaryotes due to their different chemical compositions within cellular constituents, especially the membrane lipids (Igisu et al, 2009).…”
mentioning
confidence: 99%
“…Igisu and colleagues (2006; 2009) showed that specific IR absorption peaks for aliphatic methylene (CH 2 ) and aliphatic methyl (CH 3 ) groups can be potential chemical indicators for domain‐level identification of prokaryotes. From the domain‐specific lipid components (e.g.…”
Section: Estimation Of Abundance Ratio Of Bacterial and Archaeal Cellmentioning
confidence: 99%
“…Recently, micro‐scale spectroscopic and geochemical analyses have been used to obtain the chemical signatures of a range of micrometer‐sized fossils (e.g., Alleon, Bernard, Le Guillou, Marin‐Carbonne et al., ; Brasier et al., ; House, Oehler, Sugitani, & Mimura, ; House et al., ; Kudryavtsev, Schopf, Agresti, & Wdowiak, ; Oehler et al., , , ; Schopf, Kudryavtsev, Agresti, Czaja, & Wdowiak, ; Schopf, Kudryavtsev, Agresti, Wdowiak, & Czaja, ; Ueno, Isozaki, & McNamara, ; Ueno, Isozaki, Yurimoto, & Maruyama, ; Wacey, Kilburn, Saunders, Cliff, & Brasier, ; Williford et al., ). In particular, transmission Fourier transform infrared (FTIR) microspectroscopy, which usually has a spatial resolution of more than ~10 μm, has been successfully used to analyze Proterozoic organic‐walled microfossils and Phanerozoic miospores (e.g., Arouri, Greenwood, & Walter, , ; Igisu, Nakashima, Ueno, Awramik, & Maruyama, ; Igisu et al., ; Marshall, Javaux, Knoll, & Walter, ; Steemans, Lepot, Marshall, Le Hérissé, & Javaux, ).…”
Section: Introductionmentioning
confidence: 99%